Pembelajaran seni tari kurikulum merdeka sekolah dasar ditinjau dari perspektif pendidikan seni holistik dimensi tubuh - Hesti Sastia Wahyuningsih; Karsono Karsono; Peduk Rintayati (Universitas Sebelas Maret, 2024)
This study on the implementation of dance education in the context of the Merdeka Curriculum for Grade 4 at SDN Gedongan 01 is studied from the perspective of holistic arts education. The main thing studied is the integration of the implementation of holistic arts education within the framework of the new curriculum. This study aims to describe dance arts learning in improving students' cognitive, affective, and psychomotor skills. Using a qualitative case study methodology, data were collected through observation, interviews, and document analysis involving dance educators and Grade 4 students. Based on the study, it was found that a holistic approach to dance education contributed significantly to students' physical alignment, strength, balance, and self-control, which is in line with the principle of holistic education that integrates mind, body, and soul. This approach not only improves dance movement skills but also improves students' self-confidence, cooperation, and communication skills, which provides a strong model for arts education in elementary schools. The implications of this study are to provide important information for teachers in terms of the benefits of holistic arts education for student development. The researcher's suggestion is that holistic arts education can be further integrated into further efforts by the school.